The relationship of psychological security to educational, cognitive and skill outcomes in the tennis ground for students - Shukur, Luay Hussein; Shukur, Luay Hussein; Ali, Sura Mahmood; Obaid, Ali Jalal (International Journal of Psychosocial Rehabilitation, 2020)
The need for security is one of the most important psychological needs, and one of the most important motivations for human behavior throughout life, and it is one of the basic needs necessary for normal psychological growth, psychological harmony, and mental health for the individual, and concern for the psychological security of the individual means concern for his mental health, because mental health is a permanent state that is In it the individual is compatible from a psychological, personal and social point of view with himself and with others and is able to achieve himself and invest his capabilities and potentials to the maximum extent possible, and the concern for the psychological security of the individual, whether he is an athlete or a regular person means concern for his mental health, and his personality is integrated together and his behavior is disciplined so that He lives in peace, and psychological security is one of the necessities of life that cannot continue without him, and a person needs it as his needs for food and drink. Thus, “satisfying the needs of a person is a prerequisite for obtaining the adaptation that achieves psychological stability with him.